Temporary dwellings as successful informal suburban development: The case of Sydney 1945 to 1960 - Pulan, Nicola (International Planning History Society Proceedings, 2018)
Occupation of temporary dwellings during a shortage of affordable housing is a global phenomenon. Until recently, the majority of urban planning literature has tended to convey that this type of informal urbanism existed only in the global south. However, a number of scholarly publications have revealed that informal urbanism was present in the global north throughout the early twentieth century, surrounding newly-industrialising cities in France and Canada and as seasonal accommodation in the UK. Recent studies reveal that similar dwellings emerged with illegal suburbanisation in Greek and Portuguese cities during the mid-century, and persist today as US-Mexico borderland colonia settlements. References to temporary dwellings in Australian housing literature suggested that informal urban development existed at an appreciable scale on the fringes of most towns and cities in Australia following world war two. This paper surveys the phenomenon as it played out in the outer suburbs of metropolitan Sydney, highlights a distinctive Australian story, and compares this with the international instances. The paper then suggests that a combination of four unprecedented circumstances prevailing in post-war Sydney enabled temporary dwellings to be a successful form of informal suburban development that enabled economically-marginal households to achieve ownership of a conventional home.